Changes in the gills of the European eel (Anguilla anguilla) after chronic exposure to environmental cocaine concentration. - Capaldo A; Gay F; Laforgia V (Ecotoxicology and Environmental Safety, 2019)
The recent discovery of illicit drugs in the aquatic environment has raised concerns about the possible effects on the aquatic fauna, because of the pharmacological activity of these substances. Cocaine is an illicit drug widespread in surface waters since it is the third most widely used drug in North America, Western and Central Europe, and the second in Latin America and the Caribbean. The aim of this study was to evaluate the influence of environmental concentrations of cocaine on the gills of the European eel (Anguilla anguilla). The gills of male silver eels exposed to 20 ng L-1 of cocaine for fifty days were compared to control, vehicle control and post-exposure recovery ten days groups. The following parameters were evaluated: the thickness of the interlamellar epithelium (TIE), the length of the secondary lamellae (LSL) and the fraction of the interlamellar epithelium and the secondary lamellae occupied by the mucous cells ( MC(IE-SL)FA) 3) the plasma cortisol and prolactin levels. After cocaine exposure, the gill epithelium appeared hyperplastic. The following changes were observed: proliferation in the interlamellar epithelium; partial and total fusion of the secondary lamellae, that appeared shortened and dilated; epithelial lifting and aneurism in the secondary lamellae. Moreover, in cocaine exposed eels, an increase in TIE and MC(IE-SL)FA and a decrease in LSL were observed. These changes were still present ten days after the interruption of cocaine exposure. Plasma levels of both cortisol and prolactin increased after cocaine exposure; ten days after the interruption of cocaine exposure, the plasma cortisol levels were still higher, whereas the plasma prolactin levels were lower, than control values. Our results show that even a chronic exposure to low environmental cocaine concentrations severely harms the eel gills, suggesting damages to their functions, and potentially affecting the survival of this species.